Mapping Needs: Designing English Module For Tourism And Hotel (Emth) - Dina Syarifah Nasution; Syahrul R; Mukhaiyar (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
This research aimed to identify the learning and target needs, as well as the importance of English for students in the tourism and hotel industry. Utilizing a survey method, data was collected through questionnaires and interviews with students and professionals in the hospitality sector. Listening emerged as the skill of highest priority at 83.33%, while Speaking and Reading were equally critical at 91.67%. Surprisingly, Writing was designated as High Needed at 66.67%, highlighting a pressing need for enhanced written communication. Additionally, the study revealed that